2017
DOI: 10.3390/nu9070669
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Cow’s Milk Fermented with Lactobacillus paracasei CBA L74 on Common Infectious Diseases in Children: A Multicenter Randomized Controlled Trial

Abstract: Background: Fermented foods have been proposed to prevent common infectious diseases (CIDs) in children attending day care or preschool. Objectives: To investigate the efficacy of dietary supplementation with cow’s skim milk fermented with the probiotic Lactobacillus paracasei CBA L74 in reducing CIDs in children attending day care or preschool. Methods: Multicenter, randomized, double-blind, placebo-controlled trial on healthy children (aged 12–48 months) consuming daily 7 grams of cow’s skim milk fermented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 41 publications
4
92
0
3
Order By: Relevance
“…b) Centre was found to be a significant confounder related to the low power in the Milan and Palermo centres in the study by Corsello et al (2017). b) Centre was found to be a significant confounder related to the low power in the Milan and Palermo centres in the study by Corsello et al (2017).…”
Section: Human Intervention Studiesmentioning
confidence: 76%
See 2 more Smart Citations
“…b) Centre was found to be a significant confounder related to the low power in the Milan and Palermo centres in the study by Corsello et al (2017). b) Centre was found to be a significant confounder related to the low power in the Milan and Palermo centres in the study by Corsello et al (2017).…”
Section: Human Intervention Studiesmentioning
confidence: 76%
“…The post hoc statistical re-analysis (Calame, 2018, unpublished) consists of a combined analysis with data from one study and data from each centre (n = 3) participating in the second study (Corsello et al, 2017). According to the applicant, the combined analysis aimed to: (a) increase the power of the studies by assigning a positive event to the drop-outs, and (b) identify potential heterogeneity between the two studies in order to address the multicentre approach in the study by Corsello et al (2017).…”
Section: Human Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…40 However, a recent multicenter, randomized, double-blind, placebo-controlled study revealed that the administration of fermented skim milk with Lactobacillus paracasei CBA L74 could prevent common respiratory and intestinal infections in preschool-age children (12-48 months of life). 41 Further research is needed to demonstrate the capacity of this fermented matrix to modify the neonatal microbiota, but the available data would seem to confirm its role. 42 In addition to maternal or neonatal supplementation with these functional nutrients, other methods have also been experimented to achieve effective microbiota modification.…”
Section: Possible Interventions To Modify Microbiotamentioning
confidence: 99%
“…Research evidence for numerous probiotic benefits such as obesity-related disorders, antibioticassociated diarrhea, infections, and cancer was described [3]. Corsello et al [4] stated that dietary supplementation with cow's skim milk fermented with Lactobacillus paracasei CBA L74 is an efficient strategy in preventing common infectious diseases in children.…”
Section: Introductionmentioning
confidence: 99%